Digital Transformation in Enterprise Risk Management: A Bibliometric Study and Research Trends - Judijanto, Loso; Pahrijal, Rival; Lesmana, Tera (Westscience Press, 2025)
This study examines digital transformation research using bibliometric analysis, identifying key trends, collaborative networks, and thematic areas. Findings reveal that